Thermal conductivity of hot-pressed hexagonal boron nitride. (November 2016) - Kusunose, Takafumi; Sekino, Tohru
Abstract: The thermal conductivity parallel and perpendicular to the hot-pressing direction of hot-pressed h -BN was measured to investigate the effects of oxide additive species and compositions on the thermal conductivity. CaO, MgO, Y2 O3, Yb2 O3, and their mixtures were selected as oxide additives owing to their previously demonstrated ability to enhance the thermal conductivities of non-oxide materials such as AlN and Si3 N4 . The investigated additive concentrations were calculated to be 5, 10, and 15 vol%. A thermal conductivity of approximately 210 W/m·K was attained by hot-pressing mixed powders of h -BN and a Yb2 O3 –MgO or Yb2 O3 –CaO additive at a concentration of 15 vol%. Graphical abstract: